Periphrastic causative constructions in 16th–17th c. Lithuanian - Pakerys, Jurgis (Baltistica, 2019)
This study analyzes periphrastic permissive and factitive causative constructions in a corpus of 16th and 17th century Old Lithuanian texts. In contrast to modern use, permissive constructions with duoti play a central role in many texts, while those with leisti are only more frequent in some sources and appear to have spread from the east to the west. Due to the influence of bifunctional German lassen constructions, duoti is used not only in permissive constructions, but also in factitive constructions, especially in Prussian Lithuanian. The permittees in duoti and leisti constructions are usually marked as dative, although the accusative is also attested due to the influence of German lassen + acc constructions; however, in the case of leisti, the accusative may sometimes be interpreted as archaic, marking the direct object of the source construction leisti ‘release’ + acc. In addition to permissive constructions with duoti and leisti, this paper also discusses rare cases of the archaic verb (pa-)velti and the borrowed Slavic permissives pa-velyti and pa-/pri-zvalyti. The majority of reflexive permissive constructions are based on duoti and contain a reflexive affixal marker on the matrix predicate, but constructions with an additional marker on the subordinate infinitive are also well-attested. In general, factitive constructions are less frequent than permissive ones and, just as in Modern Lithuanian, the most common factitive is (pri-)versti, but borrowed Slavic (pri-)sylyti is also attested in some sources.